Distribution of U.S. beef exports in the international market - Tenhoff, Heather (Kansas State University, 2014)
The beef industry is a very important in the food sector of agriculture and over the past two decades the United States beef industry has faced many challenges. Over time the distribution of beef exports have changed due to food safety issues and government policies, not just in the U.S., but on a global scale forcing U.S. beef producers to diversify their export outputs to other countries that were not previously strong leaders in the export business. The U.S. must be strategic in their production decisions in order to continue to compete on a global level to avoid significant loss during adverse conditions. One of the major challenges that the U.S. industry has faced is the discovery of BSE in late 2003 in the state of Washington, which led to the closing of many borders to countries who had a significant impact on the beef industry in the U.S. Since U.S. beef is highly regarded by consumers for its quality worldwide, it is important to understand what changes have taken place in the past to have a full understanding of what changes need to be made in the future. The objective of this thesis is to look at how the distribution of the value, volume and price of U.S. beef exports have changed over the past two decades. By looking at how this has changed we will be able to see what countries are emerging as important customers and how others have declined. This is extremely important since some of the major importing countries have changed or put restrictions on the U.S. beef industry over the past two decades and the industry needs to understand these changes so that they can remain strong in the export sector. By analyzing the global trends of U.S. beef exports by value, volume and price across principal regions of the world, research will show us how to change for future changes. By assessing the effect of the discovery of BSE in the U.S on changes in the distribution of beef exports across the global regions, research will show who emerged when other countries declined. By using this research, the foregoing results will be helpful to inform the industry on what export market strategy can be developed for the U.S. beef industry. The results suggest that BSE had some negative effect on the U.S. beef industry in terms of the value and volume but did not have an impact on the price per pound of beef. Some regions had a larger impact than others when BSE was discovered, such as East Asia, but during this other regions, such as North America, came through and became the leaders in exports for U.S. beef. While there was some growth from the Rest of the World, there was not enough of an impact to compete with the foregoing countries.
Keywords: BSE; Beef exports; East Asia; Economics (0501); Economics, Agricultural (0503); Economics, Commerce-Business (0505)